Internalization of the Values of Morality QS. Al-Luqmān Verses 18-19 in Adolescent Character Education in the Digitalization Era: An Approach to Tafsir Ma'nā Cūm Maghzā - Bahroin, Moh Haikal Balya Hafidzal Bahroin; Jannah, Sugiarti Khoirul; Imdadulloh, Moh Nabil (Universitas Nurul Jadid, 2025)
Technological developments are increasingly dominating in daily life. Today's generation is different from previous generations. They tend to spend their time with digital technology. Because technology has become part of daily life, it certainly raises concerns about the negative impact on the nation's young generation, especially on cognitive, moral, motor, and social development. This article aims to discuss the concept of moral educational values, in QS. Luqman 18–19 and relevant it to the moral challenges of the younger generation in the digital age using the ma'nā cūm maghzā approach. This research uses the concept of library research through the hermeneutic approach of ma'nā cūm maghzā which will be applied to Al-luqmān Verses 18-19. This approach will perform semantic analysis, look at the context of the derivative of the verse and contextualize it with digital phenomena. As a result of this study, the author obtained four main messages from the analysis, namely the prohibition of arrogance, the prohibition of being arrogant, the command to speak slowly and softly, and the command to respect the elderly. These moral education values can be a preventive effort, providing education to parents, teachers, or other communities to prevent the current young generation (alpha generation) from falling into moral degradation due to the impact of technology.